Pengembangan Bahan Ajar Elektronik Personal Hygiene Berbasis Heyzine untuk Siswa SMK Kuliner Fase E - Yuliana Dwi Pratiwi; Sri Handajani; Niken Purwidian; Andika Kuncoro Widagdo (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This study aims to determine: 1) the results of developing Heyzine-based teaching materials on personal hygiene; 2) the suitability of the materials and media; and 3) student responses to Heyzine-based teaching materials. This research follows the ADDIE method, which is conducted until the development stage (stage 3). The validation of Heyzine-based teaching materials involved two material experts and two media experts. The research encompasses Heyzine-based teaching materials and student responses. The instruments used for evaluating the feasibility of Heyzine-based teaching materials were material validation sheets and questionnaires to gauge student responses. The data analysis technique involved quantitative descriptive analysis. The results showed: 1) the development outcomes of Heyzine-based teaching materials on personal hygiene can be accessed via the following link https://heyzine.com/flip-book/8173401c86.html; 2) The materials and media were found highly feasible, with percentages of 81.7% and 84%, respectively; and 3) Student responses indicated that the teaching materials were rated very positively, with a percentage of 93.4%.